Analisis Pengaruh Faktor Situasional Terhadap Pembelian Impulsif Pada Binjai Supermall - T. Fadlanil Muflih (Universitas Islam Negeri Sumatera Utara, 2018)
This study aims to analyze factors consisting of physical environment, social environment, time perspective, and mood on impulsive purchases in Binjai Supermall. This study uses quantitative methods with 100 samples. The data used are primary and secondary data with the accidental sampling technique. The analytical tool used is multiple linear regression analysis. The t test shows the social environment and mood variable have an influence on impulsive purchase in Binjai Supermall. Physical environment variable and time perspective have no effect on impulsive purchase on Binjai Supermall. The F test show the results that the physical environment variable, social environment, time perspective, and mood influence the impulsive purchase of Binjai Supermall. from the determination test the value of R Square is 0.873 that the dependent variable on impulsive purchases can be explained by independent variables namely physical environment, social environment, time and mood perspective of 87.3% and the rest is explained by other variables.